1996
DOI: 10.1016/s0006-3495(96)79536-x
|View full text |Cite
|
Sign up to set email alerts
|

The affinities of procolipase and colipase for interfaces are regulated by lipids

Abstract: It has been suggested that at physiological pH, the trypsin-catalyzed activation of the lipase cofactor, procolipase, to colipase has no consequence for intestinal lipolysis and serves primarily to release the N-terminal pentapeptide, enterostatin, a satiety factor (Larsson, A., and C. Erlanson-Albertsson 1991. The effect of pancreatic procolipase and colipase on pancreatic lipase activation. Biochim. Biophys. Acta 1083:283-288). This hypothesis was tested by measuring the adsorption of [14C]colipase to monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…The purification of water and preparation of solvents, buffer, and lipid solutions have been previously described in Momsen et al (10). Porcine colipase used in this study was prepared and converted to [ 14 C]colipase by reductive methylation as described previously in Schmit et al (11). The [ 14 C]colipase had a specific radioactivity of 9.76 Ci/mol.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The purification of water and preparation of solvents, buffer, and lipid solutions have been previously described in Momsen et al (10). Porcine colipase used in this study was prepared and converted to [ 14 C]colipase by reductive methylation as described previously in Schmit et al (11). The [ 14 C]colipase had a specific radioactivity of 9.76 Ci/mol.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…HPL(S153G) and -polylysine were radiolabeled by reductive methylation as described for porcine colipase (14). The ratios of reagents were adjusted to compensate for the different number of free amino groups in the three proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Before use the papers were cleaned by washing them sequentially with chloroform/ methanol (2:1 v/v), chloroform, and hexane, followed by airdrying at 150 °C for 50 min (40). Procolipase was purified from porcine pancreas and converted to colipase and to [ 14 C]colipase with a specific radioactivity of 21 dpm/pmol as reported elsewhere (35). PTL (triacylglycerol acylhydrolase, EC 3.1.1.3) was purified from an extract of porcine pancreas using conventional techniques as previously described (41).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been shown that the clustering of Ca 2+ soaps of fatty acids enhances the adsorption of pancreatic lipase to interfaces (34). To help understand these effects, our laboratory investigated the interaction of colipase with monomolecular films of diacylphosphatidylcholine, free fatty acid, acylglycerols, and their mixtures (35,36). Based on data obtained in vivo, but in contrast to most of the earlier studies of PTLcolipase function, colipase-lipid interactions were characterized thermodynamically at a pH consistent with that in the intestinal lumen (37) and in the absence of calcium ion (38).…”
mentioning
confidence: 99%